2017
DOI: 10.1017/s1355617717000480
|View full text |Cite
|
Sign up to set email alerts
|

Racial Differences in Neurocognitive Outcomes Post-Stroke: The Impact of Healthcare Variables

Abstract: Objective The present study examined differences in neurocognitive outcomes among non-Hispanic Black and White stroke survivors utilizing the NIH Toolbox-Cognition Battery (NIHTB-CB), and investigated the roles of healthcare variables in explaining racial differences in neurocognitive outcomes post-stroke. Method One-hundred-seventy adults (91 Black; 79 White), who participated in a multisite study were included (Age: M=56.4, SD=12.6; Education: M=13.7, SD=2.5; 50% male; Years post-stroke: 1–18; Stroke type:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 75 publications
(102 reference statements)
0
5
0
Order By: Relevance
“…The prevalence of CSVD and risk factors for CSVD are significantly higher among African Americans compared to non-Hispanic Whites [2]. This disparity exists even after adjusting for traditional dementia risk factors and relevant covariates [3,4]. Several studies have reported on the contribution of genetic variation, such as the APOE ε4 genotype, to the incidence and prevalence of dementia and cognitive decline in both African Americans and non-Hispanic Whites [[5], [6], [7]].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of CSVD and risk factors for CSVD are significantly higher among African Americans compared to non-Hispanic Whites [2]. This disparity exists even after adjusting for traditional dementia risk factors and relevant covariates [3,4]. Several studies have reported on the contribution of genetic variation, such as the APOE ε4 genotype, to the incidence and prevalence of dementia and cognitive decline in both African Americans and non-Hispanic Whites [[5], [6], [7]].…”
Section: Introductionmentioning
confidence: 99%
“…Using such ability traits can facilitate neuropsychiatric diagnosis and treatment, as well as allow the prediction of individual risks. It can help understand contributors of different conditions, such as chronic pain (Alais et al, 2010;Vachon-Presseau et al, 2016), neurodevelopmental disorders (Barch et al, 2019), autism (Happé and Frith, 1996), stroke rehabilitation (Carlozzi et al, 2017;Johnson et al, 2017), Alzheimer's disease (Snyder et al, 2011), and other neuropsychiatric conditions (Hayden et al, 2018). While personality traits have been studied extensively (Gerlach et al, 2018), human ability, including behavioral and neurological function, is still underexplored.…”
Section: Introductionmentioning
confidence: 99%
“…13,[23][24][25] While researchers have suggested that blacks have shown poorer cognitive function following stroke, the combined contribution of stroke and dementia to race differences in disability is unknown. 26 In this context, we explore the relative impact of stroke and dementia with disability. We hypothesize that a person with both stroke and dementia will have greater disability than the sum of its parts.…”
Section: Introductionmentioning
confidence: 99%